Nali's knot in Haji Qadir Koyi's poetry - غریب, ا.م. د. له‌نجه‌ عبدالرحمن غریب (Sulaimani Journal for Humanities, 2025)
This research is entitled: (Nali's Knot in Haji Qadir Koyi's Poetry). From this point of view, Haji Qadir Koyi as a prominent poet of the second front of the Baban school of poetry is considered one of the prominent poets of his time He praises them, but in his book he mentions Nali more than any other Kurdish poet, so that this mention is repeated more than fourteen times. Although this subject has been looked at in a simple way, but by delving into the artistic and semantic structure of these lines of poetry, it is clear that Haji Qadir not only mentioned Nali's name for praise, but also had other purposes The mental knot that Nali and Nali's poetry have created in Haji Qadir's mind!. This research is a scientific and critical attempt to answer this question and prove the mental knot that the poet had towards Nali with evidence of the lines of poetry that mention Nali according to the theory of self-inferiority and compensation of Alfred Adler.
Keywords: Haji Qadir; Nali; poetry; comparison; Feelings of self inferiority